Endophytic bacteria with allelopathic potential regulate gene expression and metabolite production in host Casuarina equisetifolia - Wang, Ying; Chen, Pan; Lin, Qi; Zuo, Linzhi; Li, Lei (Frontiers in Plant Science, 2024)
Introduction: Casuarina equisetifolia is a common protective forest in coastal areas. However, artificial C. equisetifolia forests cannot self-renew, mainly due to the accumulation of allelochemicals. Endophytic bacteria may alleviate the root growth inhibition caused by allelochemicals in C. equisetifolia seedlings. B. amyloliquefaciens and B. aryabhattai were endophytic bacteria with strong allelopathy in C. equisetifolia root. The allelopathy mechanism of these two endophytes and their interaction with C. equisetifolia remains to be studied. Methods: Whole-genome sequencing of B. amyloliquefaciens and B. aryabhattai isolated from the roots of allelochemical-accumulating C. equisetifolia was performed using Illumina Hiseq and PacBio single-molecule sequencing platforms. Sterile seedlings of C. equisetifolia were treated with either individual or mixed bacterial cultures through root drenching. Transcriptional and metabolomics analyses were conducted after 3 days of infection. Results and discussion: Whole-genome sequencing of Bacillus aryabhattai and Bacillus amyloliquefaciens showed that the two strains contained various horizontal gene transfer elements such as insertion sequence, prophage and transposon. In addition, these two strains also contain numerous genes related to the synthesis and catabolism of allelochemicals. After these two strains of bacteria were individually or mixed infected with C. equisetifolia, metabolomics and transcriptomic analysis of C. equisetifolia showed the 11 important secondary metabolite biosynthesis among them alkaloids biosynthesis, phenylpropanoid and terpenes biosynthesis and related genes were putatively regulated. Correlation analysis revealed that 48 differentially expressed genes had strong positive correlations with 42 differential metabolites, and 48 differentially expressed genes had strong negative correlations with 36 differential metabolites. For example, CMBL gene showed positive correlations with the allelochemical (-)-Catechin gallate, while Bp10 gene showed negative correlations with (-)-Catechin gallate. Conclusion: The intergenerational accumulation of allelochemicals may induce horizontal gene transfer in endogenic bacteria of Casuarina equisetifolia root. Endophytic Bacillus plays an allelopathic role by assisting the host in regulating gene expression and the production and/or variety of allelochemicals. This comprehensive study sheds light on the intricate genetic and metabolic interactions between Bacillus endophytes and C. equisetifolia. These findings provide insights into endophyte-mediated allelopathy and its potential uses in plant biology and forest sustainability.